Service delivery and development at the grassroots: the evolution and contribution of community-based organisations in Nepal - Acharya, Keshav K.; Zafarullah, Habib (2017)
Community-based organisations have been well positioned to deliver community services, undertake community development activities, and enhance community governance in Nepal. These aspects of their work are addressed in this article from an institutional perspective focusing on their evolution and contribution to local public affairs. The evidence is that many are committed to being agents of change within their communities, with institutional norms, rules and values developed accordingly. But many are constrained in what they can do by socio-economic power structures and severe resource limitations, which have significant consequences for their work and achievements. - Reproduced.
Keywords: Community-based organisations - Nepal; Social service agencies - Nepal; Non governmental organizations